Non-English Majors’ Perceptions of English Proficiency Standards and CEFR-V in Tertiary Education in Vietnam (Journal of Contemporary Educational Policies and Practices, 2023)
Vietnam’s education system has made significant efforts to enhance foreign language proficiency, particularly in English, across all levels of training. In recent years, although many educational policies and projects, typically National Foreign Language Project have been promulgated and widely applied, there are still gaps and limitations. One of them is the lack of research on the beliefs and understanding of students who are most deeply affected by the English graduation standard policies. This paper aims to examine non-English major undergraduates’ understanding of the CEFR-V (a Vietnamese version of the Common European Framework of Reference for Languages) and their beliefs about the current implementation of the English proficiency standards to university students in Vietnam. The study collected data from 122 students from a large university in Vietnam. Descriptive statistics indicate that while the participants possess sufficiently positive beliefs about the implementation of the national proficiency standards for undergraduate students, there are still concerns about standardization and differentiation. Additionally, the students are found to have limited knowledge and low usage of the CEFR-V. Thereby, some suggestions were made to improve the foreign language policy and optimize students' learning outcomes.
Keywords: National Foreign Language Project; English proficiency standards; CEFR-V; tertiary education; Vietnam